Speculations on/with light-sensitive matter - Koutsomichalis, Marinos; Vaughan, Connell (My University, 2024)
This short essay discusses the Mörk Materia project that has been presented in a hybrid format combining elements of audiovisual performance, talk, and artefact exposition. The project pivots on cameraless photography and the creative utilisation of the darkroom as a creative laboratory to produce ‘stuff’ all by itself. Employing a variety of techniques, photo and non-photo chemistry, silver-gelatin film, photo-sensitive paper, and slapdash materials, all kinds of abstract imagery is created entirely from scratch. On this continuum, Mörk Materia celebrates unconditional exploration of the literal/material foundation of photography and suggests itself as a hands-on means of speculation and ontological enquiry.